Internship experience report: Ribera school (2022)
Through this paper it will explore the results of the applications of the different teaching strategies and methodologies such as flipped classroom, high- tech approach, and active learning. And explore its impact in a selected group of students in a post conflict context. Thus, the purpose of this internship aims to enhance the teaching performance in a real teaching stage, acquire the necessary skills and help future teachers to get a tool in order to cover students and school’s needs. Where I worked is the Institution of Education “La Ribera” School, located in Monteria- Cordoba. They have students from 5th to 11th grade which are encouraged by teachers to learn the target language and improve their English skill while they learn values.